2017
DOI: 10.2175/106143017x15023776270278
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection Processes

Abstract: A review of the literature published in 2016 on topics relating to disinfection processes is presented. This review is divided into the following sections: disinfection methods, disinfection byproducts (DBPs), and microbiology and microbial communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Disinfection methods for drinking water were a crucial development for public health in the 20th century, effectively controlling the spread of water-borne diseases caused by microbial pathogens. 1–5 However, disinfection is a “double-edged sword” as it can eliminate pathogenic microorganisms but also pose health risks as a result of disinfection by-products (DBPs). 6–9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disinfection methods for drinking water were a crucial development for public health in the 20th century, effectively controlling the spread of water-borne diseases caused by microbial pathogens. 1–5 However, disinfection is a “double-edged sword” as it can eliminate pathogenic microorganisms but also pose health risks as a result of disinfection by-products (DBPs). 6–9…”
Section: Introductionmentioning
confidence: 99%
“…Disinfection methods for drinking water were a crucial development for public health in the 20th century, effectively controlling the spread of water-borne diseases caused by microbial pathogens. [1][2][3][4][5] However, disinfection is a "doubleedged sword" as it can eliminate pathogenic microorganisms but also pose health risks as a result of disinfection byproducts (DBPs). [6][7][8][9] Previous research has shown that long-term exposure to DBPs in drinking water increases the risk of birth defects, developmental toxicity, and rectal and bladder cancers.…”
Section: Introductionmentioning
confidence: 99%